Dispersive liquid-liquid microextraction for the simultaneous separation of trace amounts of zinc and cadmium ions in water samples prior to flame atomic absorption spectrometry determination - Sayed Zia Mohammadi (Química Nova, 2012)
In the proposed method, carbon tetrachloride and ethanol were used as extraction and dispersive solvents. Several factors that may be affected on the extraction process, such as extraction solvent, disperser solvent, the volume of extraction and disperser solvent, pH of the aqueous solution and extraction time were optimized. Under the optimal conditions, linearity was maintained between 1.0 ng mL-1 to 1.5 mg mL-1 for zinc and 1.0 ng mL-1 to 0.4 mg mL-1 for cadmium. The proposed method has been applied for determination of trace amount of zinc and cadmium in standard and water samples with satisfactory results.